Simultaneous Ipsilateral Distal Interphalangeal and Metacarpophalangeal Dislocation of the Fifth Finger: A Rare Case Report - Suvarn Gupta1 , Vasant Gawande2 , Ankush Mohabey3 , Kunal Saoji3 , Ashwin Chavan4 (Indian Journal of Forensic Medicine & Toxicology, 2020)
There has been no case of simultaneous ipsilateral distal interphalangeal and metacarpophalangeal dislocationof little finger in the literature. We report a case of A 61 years old male patient with traumatic ipsilateraldislocation of the Dorsal Interphalangeal (DIP) joint with dislocation of the metacarpophalangeal (MP) jointof the little finger. Both the dislocations were reduced by traction and closed reduction